Analisis Sedimentasi Pada Saluran Drainase Di Kecamatan Medan Johor,Kota Medan - Lioni Gabby Ella Br Ginting; Rizky Simanjuntak; Wisnu Prayogo; Rumilla Harahap (Jurnal Ilmu Teknik Sipil Indonesia, 2026)
This study aims to examine the sedimentation condition in drainage channels located in Medan Johor District, Medan City, and to analyze its impact on channel flow capacity. The background of this research is the decreasing performance of drainage systems due to the accumulation of sediments originating from surface runoff, community activities, and solid materials transported by rainwater. The method employed in this study is a field survey involving direct measurements of channel dimensions, including length, width, depth, and sediment thickness at several observation points. The collected data were processed to estimate sediment volume using a geometric calculation approach. The analysis results indicate that the total sediment volume across seven observation segments reaches 2,180.75 m³, reflecting a relatively high level of sedimentation. This condition leads to a reduction in channel capacity, resulting in suboptimal water flow. Furthermore, population growth contributes to increased domestic wastewater entering the drainage system. If not properly managed, this situation may increase the risk of waterlogging and flooding. Therefore, sustainable drainage management and regular maintenance are essential to improve system performance.